The hydraulic resistance of mesh dividers of phases in the non-stationary liquid stream - Давыдова, Анжелика Владимировна (Eastern-European Journal of Enterprise Technologies, 2014)
The flight program of modern aircrafts includes multireclosure of propulsion system in practically zero gravity conditions. Normal start of engines in zero gravity conditions is ensured by fuel continuity means, which are an integral part of the fuel system. Today, mesh dividers of phases, the basic working element of which is a woven metal mesh with micron-sized cells are the most widely used as such means. One of the main design parameters of mesh dividers of phases is pressure loss that occurs during the passage of the fuel flow through the phase divider cells in the course of flight mission of the aircraft. The effect of the nonstationarity level of the fuel stream, flowing through the cells of the mesh at the transient operation stages of the propulsion system on the amount of pressure losses is investigated in the paper. Using an operational method, applied to the differential equation of the accelerated motion of a viscous fluid in a finite-length cylindrical tube, an equation, describing the value of hydraulic resistance coefficient of mesh divider of phases depending on the Froude and Reynolds numbers is derived. As a result, it is found that using the values of hydraulic resistance coefficient of mesh dividers of phases without considering fuel consumption nonstationarity when performing design calculations can lead to significant errors in determining pressure losses on the mesh divider of phases at transient operation stages of the propulsion system. Using the results of the work in engineering practice allows to optimize the design parameters of fuel continuity means and increase the efficiency of the fuel system of spacecrafts in various flight conditions.